Quality Improvement Of Islamic Education - Ali Akbar (Beginner: Journal of Teaching and Education Management, 2023)
Education has a very big role and at the same time is a very important resource. Especially for developing countries. Because education is a very important requirement for human life. Education will help shape personality in the future as well as having the function of developing capabilities and improving the quality of life and human dignity in Indonesia in order to realize national goals. Efforts made by teachers in overcoming strategic obstacles in improving the quality of Islamic religious education learning include improving the quality of student learning to study Islamic religious education subjects, procuring guidebooks or literature on Islamic religious education subjects, mastering learning methodologies for teachers on subjects Islamic education